From the 1986 Annual Conference - CAML Editor (CAML Review / Revue de l’ACBM, 1986)
Folklore Session summary Music therapy Session summary An annotated checklist of separately issued bibliographies and discographies of Music therapy and Psychology of music - C. Gérald Parker